Prevalence of endosalpingiosis and other benign gynecologic lesions - Sunde, Jan; Wasickanin, Morgan; Katz, Tiffany A.; Wickersham, Emily L.; Steed, D. O. Emilie; Simper, Novae (PLOS ONE, 2020)
Endosalpingiosis, traditionally regarded as an incidental pathological finding, was recently reported to have an association with gynecologic malignancies. To determine the prevalence of endosalpingiosis, we evaluated all benign appearing adnexal lesions using the Sectioning and Extensively Examining-Fimbria (SEE-Fim) protocol, and queried the pathology database for the presence of endosalpingiosis, gynecologic malignancy, endometriosis, Walthard nests, and paratubal cysts. Using the SEE-Fim protocol, the prevalence of endosalpingiosis, endometriosis, Walthard nests, and paratubal cysts were 22%, 45%, 33%, and 42% respectively, substantially higher than previously reported. All lesions were observed to increase with age except endometriosis which increased until menopause then decreased dramatically. Among specimens including ovarian tissue, the prevalence of implantation of at least one lesion type was ubiquitous in patients age 51 and older (93%). The clinical significance of endosalpingiosis should be a continued area of research with larger trials assessing prevalence, factors affecting incidence, and association with malignancy. Our findings contribute to elucidating the origin of ectopic lesions and gynecologic disease risk.